Β6-Integrin Serves as a Potential Serum Marker for Diagnosis and Prognosis of Pancreatic Adenocarcinoma. Issue 8 (13th August 2021) - Lenggenhager, Daniela; Bengs, Susan; Fritsch, Ralph; Hussung, Saskia; Busenhart, Philipp; Endhardt, Katharina; Töpfer, Antonia; The, Frans Olivier; Bütikofer, Simon; Gubler, Christoph; Scharl, Michael; Morell, Bernhard
Abstract : INTRODUCTION: Despite enormous efforts during the past decades, pancreatic adenocarcinoma (PAC) remains one of the most deleterious cancer entities. A useful biomarker for early detection or prognosis of PAC does not yet exist. The goal of our study was the characterization of β6 -integrin (ITGB6) as a novel serum tumor marker for refined diagnosis and prognosis of PAC. Serum ITGB6 levels were analyzed in 3 independent PAC cohorts consisting of retrospectively and prospectively collected serum and/or (metastatic) PAC tissue specimens. METHODS: Using 2 independent cohorts, we measured serum ITGB6 concentrations in 10 chronic pancreatitis patients, 10 controls, as well as in 27 (cohort 1) and 24 (cohort 2) patients with PAC, respectively. In these patients, we investigated whether ITGB6 serum levels correlate with known clinical and prognostic markers for PAC and whether they might differ between patients with PAC or benign inflammatory diseases of the pancreas. RESULTS: We found that elevated serum ITGB6 levels (≥0.100 ng/mL) in patients suffering from metastasizing PAC presented an unfavorable prognostic outcome. By correlating the ITGB6 tissue expression in primary and metastatic PAC with clinical parameters, we found that positive ITGB6 expression in the tumor tissue is linked to increased serum ITGB6 levels in nonmetastatic PAC and correlates with carbohydrate antigen 19-9 and clinical outcome. DISCUSSION: Our findings suggest that ITGB6 might serve as a novel serum biomarker for early diagnosis and prognosis of PAC. Given the limited specificity and sensitivity of currently used carbohydrate antigen 19-9–based assays, ITGB6 may have the potential to improve the diagnostic accuracy for PAC.